Driving home - Ulfahzatul Tysha Sher Zaman (2015)
Driving Home is a short film about Salleh, a simple man who finds that his life does not seem so simple anymore. Father to a son he no longer understands, he avoids the complications in life by burying himself in work. However, as a taxi driver, work is unfortunately not that monotonous. Going to various places and meeting all kinds of people, a seemingly regular day ends up changing the way he sees the world. Armed with new ways of thinking, he drives home to his son with a new truth: that life is always simple.